2016
DOI: 10.1002/bip.22979
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and transport characteristics of swollen chitosan‐based proton exchange membranes studied by molecular modeling

Abstract: Chitosan biopolymer has been extensively applied in direct methanol fuel cells (DMFCs) as a potential replacement to conventional Nafion membrane for its considerably reduced methanol crossover. Here, we computationally explored the influences of methanol concentration, temperature, and pH parameters upon the nanostructure and dynamics, particularly the methanol crossover, in chitosan proton-exchange membrane (PEM) through molecular dynamics simulations. Theoretical results demonstrated the increased swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…As shown in Figure c, the RDFs for DOX oxygen atoms with respect to serotonin monomer, dimer, and tetramer oxygen atoms showed heightened first peaks, particularly for serotonin and dimer-1 at 2.62–2.97 Å. These peak positions are within the distances required for hydrogen-bonding interactions between oxygenated sites in DOX and serotonin species.…”
Section: Results and Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…As shown in Figure c, the RDFs for DOX oxygen atoms with respect to serotonin monomer, dimer, and tetramer oxygen atoms showed heightened first peaks, particularly for serotonin and dimer-1 at 2.62–2.97 Å. These peak positions are within the distances required for hydrogen-bonding interactions between oxygenated sites in DOX and serotonin species.…”
Section: Results and Discussionmentioning
confidence: 77%
“…Both the potential energy and temperature of all simulated cells stabilized with negligible fluctuations, indicating that equilibria had been reached. 8284 The final structures of DOX on the surfaces of serotonin and its dimers and tetramers are shown in Figure 6b, which were obtained from the last step of the MD simulations. When these snapshots were compared with the corresponding initial cells (Figure S8), we found that DOX distances relative to all serotonin substrates were significantly reduced, which suggests the tendency of DOX molecules to adsorb on all investigated surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual examinations simply exhibit that Chs polymers are more stretched in pure system compared to those blended with HEC. This structural change was quantified through radius of gyration ( R g ) prediction, as used in an earlier study Figure b displays the time evolution of R g for Chs and HEC chains.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The intermolecular interactions between Chs and HEC chains likely occur among their functional moieties. For this purpose, to gain a deeper understanding of the underlying interactions of the bindings between Chs and HEC, radial distribution function (RDF, also called g ( r )) analyses were done for various Chs and HEC functional groups responsible for their interactions . RDFs were calculated for amine −NH 2 , backbone hydroxyl (−OH1), and hydroxyl in hydroxymethyl group (−OH2) in Chs and backbone hydroxyl (−OH1) and side chain hydroxyl (−OH2) in HEC chains.…”
Section: Results and Discussionmentioning
confidence: 99%